Female nursing students' knowledge, attitudes, beliefs and behaviors toward smoking: A cross-sectional study in Saudi Arabia - Ahmad Hasan Abu Raddaha; Amirat Ali Al-Sabeely (Tehran University of Medical Sciences, 2022)
Background & Aim: Tobacco use is a leading cause or contributor to several chronic health illnesses. Smokers should be encouraged to quit smoking by healthcare providers. Nursing students represent a substantial part of the health delivery workforce in the future. It is crucial to know their knowledge and involvement in tobacco smoking control. We investigate smoking knowledge, attitudes, beliefs, and behaviors toward tobacco smoking among undergraduate nursing program female students. Methods & Materials: A cross-sectional, descriptive correlational design was used to achieve the study aims. The subjects were 134 female undergraduate nursing students who were recruited in 2016 from a school in a governmental university located in Riyadh, Saudi Arabia. A questionnaire that included the Global Health Professional Student Survey along with additional relevant questions was utilized. Results: Throughout their lifetime, 80.6% reported not smoking any type of tobacco product (never called smokers), and 19.4% reported smoking either cigarettes or waterpipes (called smokers ever). Female nursing students were less likely to become smokers if they thought that a smoker who quits smoking would 'very likely' or 'likely' avoid or decrease serious health problems [OR: 8.08 (95% CI: 2.00, 32.70), p = < 0.01]. Whereas students who were allowed to smoke at home, or were allowed to smoke in the presence of children, were more likely to become smokers. Conclusion: Knowledge about the harmful consequences of smoking alone was not enough to motivate smokers to quit. Nursing students should receive training on smoking cessation techniques.